Two Mutually Exclusive Concepts of Harm? Retrospective and Structural Wrongful Harm at the Bases of a Compensatory-Based Approach for Loss and Damage. Issue 3 (2nd September 2018) - García-Portela, Laura
ABSTRACT: Compensatory approaches to climate justice rely on powerful intuitions regarding responsibility and injustice. They appeal to one of our most deeply ingrained moral principles: those who have caused harm are those who should prima facie bear the responsibility of remedying it. However, in the context of climate change there are important epistemic and normative arguments that speak against applying this sort of principles. In this paper, I use the new developments of the science of attribution to reply to the epistemic concerns. I also provide countervailing normative reasons (based on recognition and self-respect) for the application of compensatory principles. I argue that the combination of two notions of wrongful harm — interactional and structural — would enable us to make the most of the normative force of an argument in favour of a compensatory view of climate justice.